A gap coupled hexagonal split ring resonator based metamaterial for S-band and X-band microwave applications - Shahidul Islam M.; Samsuzzaman M.; Beng G.K.; Misran N.; Amin N.; Islam M.T. (Institute of Electrical and Electronics Engineers Inc., 2023)
Metamaterials; Microwave resonators; Microwaves; Optical resonators; Refractive index; Effective medium; Effective parameters; Electrical length; Microwave applications; Negative refractive index; Split ring resonator; Split-ring resonators (SRR); Transmission frequencies; Ring gages